The interwoven sources of dreams - Barcaro, Umberto (Karnac, 2010)
The subject of this book is the study of dreaming from a specific point of view, one that provides useful and enlightening results: the analysis of the complex patterns of links among the memory sources of dreams. The significance of these patterns is logical and emotional at the same time. This approach is interdisciplinary: it directly involves the fields of psychology, psychotherapy, linguistics, computer science, mathematics (graph theory), history of psychology, literature, and motion pictures. However, no specific advanced expertise in any of these fields is required for understanding th.